Advanced Pancreatic Cancer: Flourishing Novel Approaches in the Era of Biological Therapy. (12th August 2014) - Chiu, Joanne W.; Wong, Hilda; Leung, Roland; Pang, Roberta; Cheung, Tan‐To; Fan, Sheung‐Tat; Poon, Ronnie; Yau, Thomas
Abstract : The progress in the development of systemic treatment for advanced pancreatic cancer (APC) has been slow. The mainstream treatment remains using chemotherapy including gemcitabine, FOLFIRINOX, and nab ‐paclitaxel. Erlotinib is the only approved biological therapy with marginal benefit. Studies of agents targeting epidermal growth factor receptor, angiogenesis, and RAS signaling have not been satisfying, and the usefulness of targeted therapy in APC is uncertain. Understanding in molecular processes and tumor biology has opened the door for new treatment strategies such as targeting insulin‐like growth factor 1 receptor, transforming growth factor β, phosphoinositide 3‐kinase/AKT/mammalian target of rapamycin pathway, and Notch pathway. New directions also include the upcoming immunotherapy and many novel agents that act on the microenvironment. The practice of personalized medicine using predictive biomarkers and pharmacogenomics signatures may also enhance the effectiveness of existing treatment. Future treatment approaches may involve comprehensive genomic assessment of tumor and integrated combinations of multiple agents to overcome treatment resistance. Abstract : This paper provides a comprehensive review in the current development of new treatment strategies, supported with concise scientific background and brief descriptions of ongoing phase II/III clinical trials. It provides both nonspecialists and specialists in pancreatic cancer care an overview of the topic that they can easily reference in their clinical practice or research.